Metal cluster in-situ embedding-based MOF / COF composite material as well as preparation method and application thereof

By embedding metal clusters in situ in the MOF/COF composite, the existing problems of low photocatalytic activity and poor selectivity are solved, and the efficiency and selectivity of water decomposition hydrogen production and biomass hydrogenation reaction are significantly improved.

CN119237015AActive Publication Date: 2025-01-03NORTHWESTERN POLYTECHNICAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411417327.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-03
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing photocatalytic activity functional catalysts have low catalytic activity and poor selectivity of target products, making it difficult to achieve efficient water decomposition and hydrogenation reactions for hydrogenation and biomass.

Method used

By embedding metal clusters in situ in MOF/COF composite materials, a solution containing metal particles is prepared by laser beam irradiation and ultrasonic assisted technology, and solvents such as glacial acetic acid and homotritylene are combined to carry out solvothermal reactions to form metal clusters in situ Embedded MOF/COF composites improve light capture capability and charge carrier separation kinetics.

Benefits of technology

It significantly improves catalytic activity and product selectivity, enhances the hydrolysis kinetics and the hydrogenation rate of biomass derivatives, inhibits the COF layer slippage and active site escape behavior, and improves the electron and hole separation ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237015A_ABST
    Figure CN119237015A_ABST
Patent Text Reader

Abstract

The invention discloses an MOF / COF composite material based on metal cluster in-situ embedding as well as a preparation method and application thereof, which are used for solving the technical problems of low catalytic activity and poor target product selectivity of an existing functional catalyst with photocatalytic activity. The preparation method of the MOF / COF composite material based on metal cluster in-situ embedding comprises the steps that a metal target material is obtained, and a metal cluster solution is obtained according to the metal target material; the preparation method comprises the following steps: adding a metal salt and an organic ligand into N, N-dimethylformamide, uniformly mixing, adding a glacial acetic acid aqueous solution, and reacting to obtain an MOF material; dissolving the MOF material and a COF monomer in a mixed solvent of mesitylene and 1, 4-dioxane, adding glacial acetic acid, and performing solvothermal reaction to obtain an MOF / COF composite material; and adding the MOF / COF composite material and mesitylene into a metal cluster solution, uniformly mixing, adding glacial acetic acid, performing solvothermal reaction, and cooling to obtain the metal cluster in-situ embedded MOF / COF composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photo-thermal catalytic material preparation, and more specifically, to a MOF / COF composite material based on in-situ embedding of metal clusters, a preparation method and an application thereof. Background Art

[0002] Photocatalytic water splitting to produce hydrogen and green hydrogen transfer storage is an efficient integration of solar energy to chemical energy conversion and application, and has excellent application prospects in sustainable energy utilization and conversion. As an abundant and cheap clean energy in nature, solar energy can drive energy upgrading and conversion. However, the utilization rate of solar water splitting to produce hydrogen is unsatisfactory due to the limited photon utilization of the reaction system and the slow carrier separation kinetics. At the same time, the storage of the produced green hydrogen is limited by technology and has always been one of the great challenges in the industry.

[0003] Biomass derivatives can be converted into high-value chemicals and fuels through hydrogenation reactions, which can greatly increase human demand for materials. Inspired by this, solar water splitting to produce hydrogen and biomass hydrogenation can be connected in series, which is expected to achieve efficient conversion of solar energy into new energy and chemicals. However, the integration of this series reaction puts higher requirements on the design and preparation of multifunctional catalytic materials. In recent years, representative studies have designed a small number of multifunctional catalysts, which have made great progress in the photo-thermal catalytic water splitting to produce hydrogen and the high-value conversion of biomass. Functional catalysts with different photocatalytic activities, such as metal-free semiconductor polymers, photoactive metal-organic framework materials (MOFs), covalent organic frameworks (COFs), and multi-component composite catalysts, have been widely studied in the photocatalytic water splitting to produce hydrogen and the catalytic hydrogenation of furfural. However, since the active components are easily detached from the catalytic system and the utility of the functional catalyst cannot be maximized, these single strategies are difficult to fundamentally solve the technical problems of low catalytic activity and poor selectivity of target products. Summary of the invention

[0004] The purpose of the present invention is to provide a MOF / COF composite material based on in-situ embedding of metal clusters, a preparation method and an application thereof, so as to solve the technical problems that the existing functional catalysts with photocatalytic activity have low catalytic activity and poor selectivity of target products. In view of this, the present invention is implemented by the following scheme.

[0005] In a first aspect, the present invention provides a method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters, comprising: Obtaining a metal target material, placing the metal target material in 1,4-dioxane, and irradiating the metal target material with a laser beam under the assistance of ultrasound to obtain a metal cluster solution containing metal particles; Add metal salt and organic ligand to N,N-dimethylformamide, mix well, add glacial acetic acid aqueous solution, and react at a temperature of 100-130° C. for 12-24 hours to obtain MOF material; The MOF material and COF monomer are dissolved in a mixed solvent of mesitylene and 1,4-dioxane, and glacial acetic acid is added, and after freezing and vacuuming, the solvent thermal reaction is performed for 48 to 72 hours to obtain a MOF / COF composite material; The MOF / COF composite material and mesitylene are added to the metal cluster solution, mixed evenly, and then glacial acetic acid is added. The mixture is subjected to solvent thermal reaction at a temperature of 100 to 130° C. for 48 to 72 hours. After cooling, a MOF / COF composite material with metal clusters embedded in situ is obtained.

[0006] Compared with the prior art, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, after obtaining the metal target material, the metal target material is placed in 1,4-dioxane, and the metal target material is irradiated with a laser beam to obtain a metal cluster solution containing metal particles, and the metal particles can be prevented from agglomerating in 1,4-dioxane under the assistance of ultrasound; in the process of obtaining the MOF material, the metal ions and the organic ligands are combined through coordination bonds to form a MOF material with a network structure, and the addition of glacial acetic acid aqueous solution can increase the reaction rate; in the process of obtaining the MOF / COF composite material, equal volumes of mesitylene and 1,4-dioxane with good solubility are used as a mixed solvent to dissolve the MOF material and the COF monomer, and glacial acetic acid is added Acid can increase the reaction rate and promote the polymerization reaction of COF monomers, so that COF monomers undergo polymerization reaction on the surface or inside of MOF materials to obtain MOF / COF composite materials. In this process, the mixed solution is subjected to freeze-vacuum treatment to remove possible impurities such as oxygen and moisture in the mixed solution, thereby improving the purity and efficiency of the reaction. In the process of adding MOF / COF composite materials and mesitylene to the metal cluster solution, the metal cluster solution (colloid) can replace 1,4-dioxane in the MOF / COF composite material in situ by controlling the temperature and time of the solvent thermal reaction to obtain a MOF / COF composite material with metal clusters embedded in situ. In this process, the addition of glacial acetic acid can improve the efficiency of the solvent thermal reaction. Through the above technical scheme of the present invention, the light capture ability of MOF / COF materials is regulated and improved, the separation kinetics of charge carriers is improved, the water decomposition kinetics and the hydrogenation rate of biomass derivatives are promoted. Specifically, through the above technical scheme of the present invention, metal clusters are embedded in MOF / COF in situ, and the MOF / COF materials anchor the metal clusters to the MOF / COF skeleton or interlayer through the pore or interlayer confinement effect, thereby improving the light capture ability of MOF / COF materials and improving the shortcomings of insufficient catalytic active sites. Further, the slippage of the COF layer in the MOF / COF material and the escape behavior of the active site due to insufficient anchoring sites can be suppressed, and the adsorption and activation of water molecules and reactant furfural molecules at the active center are effectively promoted, thereby significantly enhancing the separation ability of electrons and holes and improving the rate of furfural hydrogenation reaction. Through the above technical scheme of the present invention, the technical problems of low catalytic activity and poor selectivity of target products in existing functional catalysts with photocatalytic activity are solved.

[0007] Furthermore, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, the metal target includes one or more of a platinum target, a copper target, a cobalt target and a nickel target; and / or the metal target is a metal wafer.

[0008] Furthermore, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, the metal salt comprises zirconium chloride, ferric chloride, hydrated copper nitrate and tetraisopropyl titanate; and / or, The organic ligands include 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid and 2-hydroxyterephthalic acid.

[0009] Furthermore, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, the COF monomer comprises trialdehyde phloroglucinol and p-phenylenediamine; and / or, In the process of adding the MOF / COF composite material and mesitylene into the metal cluster solution, the mass ratio of the metal cluster solution to the MOF / COF composite material is 1:(4-6), and the volumes of the mesitylene and the metal cluster solution are equal.

[0010] Furthermore, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, the metal cluster solution is a colloidal solution; and / or, The content of metal particles in the metal cluster solution is 0.05-0.5wt%.

[0011] Furthermore, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, in the process of irradiating the metal target material with a laser beam under the assistance of ultrasound, the laser beam includes an unfocused laser beam; and / or, The output wavelength of the laser beam is 1064nm, the pulse frequency is 20-40Hz, the output spot diameter is 5-10mm, and the energy density of the laser beam irradiation is 800-1600mJ / cm 2 , irradiation time is 10~30min; and / or, The temperature of the 1,4-dioxane is -20-0°C, and the frequency of the ultrasound is 20-40kHz.

[0012] Furthermore, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, in the process of adding the metal salt and the organic ligand to N,N-dimethylformamide, the mass ratio of the metal salt to the organic ligand is 1:(1-3), and the mass ratio of the N,N-dimethylformamide to the metal salt is 1:(2-6); and / or, The mass ratio of glacial acetic acid to water in the glacial acetic acid aqueous solution is 1: (40-60).

[0013] Furthermore, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, the MOF material and the COF monomer are dissolved in a mixed solvent of mesitylene and 1,4-dioxane, the mass ratio of the MOF material to the COF monomer is 1:(1-5), the mass ratio of the MOF material to the 1,4-dioxane is 1:(0.03-0.1), and the volumes of mesitylene and the 1,4-dioxane in the mixed solvent are equal; and / or, In the MOF / COF composite material in which the metal clusters are in-situ embedded, the mass ratio of the MOF material to the COF material is 1:(1-5), and the mass ratio of the metal to the MOF material is 1:(200-2000).

[0014] In a second aspect, the present invention provides a MOF / COF composite material based on in-situ embedding of metal clusters, which is prepared using the above-mentioned method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters; in the MOF / COF composite material based on in-situ embedding of metal clusters, the mass ratio of MOF material to COF material is 1: (1~5), and the mass ratio of metal to the MOF material is 1: (200~2000).

[0015] Compared with the prior art, the beneficial effects of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention are the same as the beneficial effects of the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters described in the above technical scheme, which will not be repeated here.

[0016] In a third aspect, the present invention provides the application of the above-mentioned MOF / COF composite material based on in-situ embedding of metal clusters in photocatalytic water decomposition and furfural aqueous phase hydrogenation reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 A schematic diagram of the application process of the MOF / COF composite material with in-situ embedding of metal clusters of the present invention; Figure 2 This is a scanning electron microscope schematic diagram of the MOF material UiO-66-NH2 in Example 1 of the present invention; Figure 3 This is a scanning electron microscope schematic diagram of the COF material TPPa-1-COF in Example 1 of the present invention; Figure 4A transmission electron microscopy diagram of the MOF / COF composite material Pt@MOF / COF in which metal clusters are in situ embedded at 50 nm in Example 1 of the present invention; Figure 5 A transmission electron microscopy diagram of the MOF / COF composite material Pt@MOF / COF in which metal clusters are in situ embedded at 20 nm in Example 1 of the present invention; Figure 6 This is a schematic diagram of a scanning electron microscope of a MOF / COF composite material in which metal clusters are in situ embedded in Example 1 of the present invention; Figure 7 This is a physical schematic diagram of the MOF / COF composite material in which metal clusters are in situ embedded in Example 1 of the present invention; Figure 8 This is a schematic diagram of a scanning electron microscope of a MOF / COF composite material in which metal clusters are in situ embedded in Example 2 of the present invention; Fig. 9 This is a physical schematic diagram of a MOF / COF composite material in which metal clusters are in situ embedded in Example 2 of the present invention; Fig.10 This is a schematic diagram of a scanning electron microscope of a MOF / COF composite material in which metal clusters are in situ embedded in Example 3 of the present invention; Fig.11 This is a physical schematic diagram of a MOF / COF composite material in which metal clusters are in situ embedded in Example 3 of the present invention; Fig.12 Schematic diagram of the photocatalytic water splitting performance of the MOF / COF composite material with different metal clusters embedded in situ in the present invention; Fig.13 Schematic diagram of the furfural aqueous phase hydrogenation performance of the MOF / COF composite material with different metal clusters in situ embedded in the present invention. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0019] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.

[0020] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The meaning of "several" is one or more, unless otherwise clearly and specifically defined.

[0021] Biomass derivatives can be converted into high-value chemicals and fuels through hydrogenation reactions, which can greatly increase human demand for materials. Inspired by this, solar water splitting to produce hydrogen and biomass hydrogenation can be connected in series, which is expected to achieve efficient conversion of solar energy into new energy and chemicals. However, the integration of this series reaction puts higher requirements on the design and preparation of multifunctional catalytic materials. In recent years, representative studies have designed a small number of multifunctional catalysts, which have made great progress in the photo-thermal catalytic water splitting to produce hydrogen and the high-value conversion of biomass. Functional catalysts with different photocatalytic activities, such as metal-free semiconductor polymers, photoactive metal-organic framework materials (MOFs), covalent organic frameworks (COFs), and multi-component composite catalysts, have been widely studied in the photocatalytic water splitting to produce hydrogen and the catalytic hydrogenation of furfural. However, since the active components are easily detached from the catalytic system and the utility of the functional catalyst cannot be maximized, these single strategies are difficult to fundamentally solve the technical problems of low catalytic activity and poor selectivity of target products.

[0022] In order to solve the above technical problems, in a first aspect, the present invention provides a method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters, comprising: Obtaining a metal target material, placing the metal target material in 1,4-dioxane, and irradiating the metal target material with a laser beam under the assistance of ultrasound to obtain a metal cluster solution containing metal particles; Add metal salt and organic ligand to N,N-dimethylformamide, mix well, add glacial acetic acid aqueous solution, and react at a temperature of 100-130° C. for 12-24 hours to obtain MOF material; The MOF material and COF monomer are dissolved in a mixed solvent of mesitylene and 1,4-dioxane, and glacial acetic acid is added, and after freezing and vacuuming, the solvent thermal reaction is performed for 48 to 72 hours to obtain a MOF / COF composite material; The MOF / COF composite material and mesitylene are added to the metal cluster solution, mixed evenly, and then glacial acetic acid is added. The mixture is subjected to solvent thermal reaction at a temperature of 100 to 130° C. for 48 to 72 hours. After cooling, a MOF / COF composite material with metal clusters embedded in situ is obtained.

[0023] In the case of adopting the above technical scheme, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, after obtaining the metal target material, it is placed in 1,4-dioxane, and the metal target material is irradiated with a laser beam to obtain a metal cluster solution containing metal particles, and the metal particles can be prevented from agglomerating in 1,4-dioxane under the assistance of ultrasound; in the process of obtaining the MOF material, the metal ions and the organic ligands are combined through coordination bonds to form a MOF material with a network structure, and the addition of glacial acetic acid aqueous solution can increase the reaction rate; in the process of obtaining the MOF / COF composite material, equal volumes of mesitylene and 1,4-dioxane with good solubility are used as a mixed solvent to dissolve the MOF material and the COF monomer , adding glacial acetic acid can increase the reaction rate, promote the polymerization reaction of COF monomer, and make COF monomer undergo polymerization reaction on the surface or inside of MOF material to obtain MOF / COF composite material. In this process, impurities such as oxygen and water in the mixed solution can be removed by freezing and vacuuming the mixed solution, thereby improving the purity and efficiency of the reaction; in the process of adding MOF / COF composite material and mesitylene to the metal cluster solution, by controlling the temperature and time of the solvent thermal reaction, the metal cluster solution (colloid) can replace 1,4-dioxane in the MOF / COF composite material in situ to obtain a MOF / COF composite material with metal clusters embedded in situ; in this process, adding glacial acetic acid can improve the efficiency of the solvent thermal reaction. Through the above technical scheme of the present invention, the light capture ability of MOF / COF materials is regulated and improved, the separation kinetics of charge carriers is improved, the water decomposition kinetics and the hydrogenation rate of biomass derivatives are promoted. Specifically, through the above technical scheme of the present invention, metal clusters are embedded in MOF / COF materials in situ, and MOF / COF materials anchor metal clusters to MOF / COF skeletons or interlayers through pore or interlayer confinement effects, thereby improving the light capture ability of MOF / COF materials and improving the shortcomings of insufficient catalytic active sites. Further, the slippage of the COF layer in the MOF / COF material and the escape behavior of the active site due to insufficient anchoring sites can be suppressed, and the adsorption and activation of water molecules and reactant furfural molecules at the active center are effectively promoted, thereby significantly enhancing the separation ability of electrons and holes and improving the rate of furfural hydrogenation reaction. Through the above technical scheme of the present invention, the technical problems of low catalytic activity and poor selectivity of target products in existing functional catalysts with photocatalytic activity are solved.

[0024] As a possible implementation mode, in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, the metal target includes one or more of a platinum target, a copper target, a cobalt target and a nickel target; and / or the metal target is a metal wafer.

[0025] In the case of adopting the above technical solution, in the preparation method of the MOF / COF composite material based on the in-situ embedding of metal clusters of the present invention, the MOF / COF composite material with different catalytic properties or catalytic uses can be prepared by selecting the above different types of metal targets. The metal target can be a metal disc during the laser beam irradiation process; it should be noted that the type of metal target can also be reasonably selected according to the design principle of the catalytic active center, and the oxide layer or impurities that may exist on the surface of the metal target can be removed by surface treatment. The surface treatment method can be polishing or cleaning. When the cleaning method is adopted, the metal target is placed in a cleaning solution and ultrasonically treated for 30 minutes at a frequency of 10kHz. After the cleaning is completed, the metal target is placed in 1,4-dioxane (Diox) and laser beam pretreatment is performed to further remove impurities that may exist on its surface. For the above metal target, its purity is 99.999%.

[0026] It should be understood that in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, by selecting different types of metal salts and organic ligands, MOF materials that meet different usage conditions can be obtained; illustratively, the metal salts include zirconium chloride, ferric chloride, hydrated copper nitrate and tetraisopropyl titanate, and the organic ligands include 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid and 2-hydroxyterephthalic acid; as another example, the metal salts can be zirconium chloride, ferric chloride, hydrated copper nitrate and tetraisopropyl titanate, and the organic ligands can be 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid and 2-hydroxyterephthalic acid.

[0027] It should also be understood that in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, COF materials that meet different usage conditions can be obtained by selecting different types of COF monomers, and in order to make the prepared composite material have good catalytic activity and target product selectivity, the mass ratio of the metal cluster solution to the MOF / COF composite material should also be controlled within a reasonable range; exemplarily, the COF monomer includes trialdehyde phloroglucinol and p-phenylenediamine, and the mass ratio of the metal cluster solution to the MOF / COF composite material is 1: (4~6); as another example, the COF monomer can be trialdehyde phloroglucinol and p-phenylenediamine, and the mass ratio of the metal cluster solution to the MOF / COF composite material is 1:4, 1:5 or 1:6. For the metal cluster solution, the metal cluster solution is a colloidal solution, and the content of metal particles in the metal cluster solution can be 0.05-0.5wt%. As another example, the content of metal particles in the metal cluster solution can be 0.05wt%, 0.1wt%, 0.25wt%, 0.4wt% or 0.5wt%.

[0028] It should be understood that in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, in the process of irradiating the metal target with a laser beam, in order to improve the irradiation (or bombardment) efficiency of the laser beam on the metal target and obtain a metal cluster solution with uniformly dispersed metal particles, the type of laser beam and the performance parameters of the laser beam should also be controlled; for example, the laser beam includes an unfocused laser beam, and with respect to the performance of the laser beam, the output wavelength of the laser beam can be 1064nm, the pulse frequency can be 20-40Hz, the output spot diameter can be 5-10mm, and the energy density of the laser beam irradiation can be 800-1600mJ / cm 2 The irradiation time can be 10 to 30 minutes. In another example, the laser beam can be a non-focused laser beam, the pulse frequency can be 20 Hz, 30 Hz or 40 Hz, the output spot diameter can be 5 mm, 8 mm or 10 mm, and the energy density of the laser beam irradiation can be 800 mJ / cm 2 、1300mJ / cm 2 or 1600mJ / cm 2 , the irradiation time can be 10min, 20min or 30min; further, the laser beam irradiation of the metal target is carried out under the assistance of ultrasound, and the ultrasonic assistance can prevent the metal particles generated by the laser beam irradiation of the metal target from agglomerating or aggregating in 1,4-dioxane, thereby affecting the subsequent embedding effect. In this process, the temperature of 1,4-dioxane can also be controlled to further disperse the metal particles evenly in 1,4-dioxane; illustratively, the frequency of ultrasound can be 20~40kHz, and the temperature of 1,4-dioxane can be -20~0℃. In another example, the frequency of ultrasound can be 20kHz, 30kHz or 40kHz, and the temperature of 1,4-dioxane can be -20℃, -10℃, -5℃ or 0℃.

[0029] It should also be understood that in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, in the process of adding metal salts and organic ligands to N,N-dimethylformamide, N,N-dimethylformamide is the solvent for the metal salts and organic ligands, and the addition of glacial acetic acid aqueous solution can improve the preparation efficiency of the MOF material. In order to obtain a MOF material with good performance, the mixing amount or addition amount of N,N-dimethylformamide, metal salt and organic ligand should also be controlled within a reasonable range. For example, the mass ratio of the metal salt to the organic ligand can be 1: (1-3), and the mass ratio of the N,N-dimethylformamide to the metal salt can be 1: (2-6); for another example, the mass ratio of the metal salt to the organic ligand can be 1: 1, 1: 2 or 1: 3, and the mass ratio of the N,N-dimethylformamide to the metal salt can be 1: 2, 1: 4 or 1: 6; in the process of adding glacial acetic acid aqueous solution to improve the preparation efficiency of MOF materials, for example, the mass ratio of glacial acetic acid to water in the glacial acetic acid aqueous solution is 1: (40-60), and for another example, the mass ratio of glacial acetic acid to water in the glacial acetic acid aqueous solution is 1: 40, 1: 50 or 1: 60.

[0030] It should also be understood that in the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention, the MOF material and the COF monomer are dissolved in a mixed solvent of mesitylene and 1,4-dioxane. In order to obtain a MOF / COF composite material with good performance, the mass ratio of the MOF material to the COF monomer, the addition amount of 1,4-dioxane and mesitylene should also be controlled to be within a reasonable range. For example, the mass ratio of the MOF material to the COF monomer can be 1: (1~5), the mass ratio of the MOF material to the 1,4-dioxane can be 1: (0.03~0.1), and the volume of mesitylene and the 1,4-dioxane in the mixed solvent is equal. For another example, the mass ratio of the MOF material to the COF monomer can be 1: 1, 1: 3 or 1: 5, and the mass ratio of the MOF material to the 1,4-dioxane can be 1: 0.03, 1: 0.05 or 1: 0.1.

[0031] In a second aspect, the present invention provides a MOF / COF composite material based on in-situ embedding of metal clusters, which is prepared using the above-mentioned method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters; in the MOF / COF composite material based on in-situ embedding of metal clusters, the mass ratio of MOF material to COF material is 1: (1~5), and the mass ratio of metal to the MOF material is 1: (200~2000).

[0032] In the case of adopting the above technical scheme, the MOF / COF composite material based on in-situ embedding of metal clusters of the present invention is prepared by the preparation method of the MOF / COF composite material based on in-situ embedding of metal clusters. In the preparation method, after obtaining the metal target material, it is placed in 1,4-dioxane, and the metal target material is irradiated with a laser beam to obtain a metal cluster solution containing metal particles. Under the assistance of ultrasound, the metal particles can be prevented from agglomerating in 1,4-dioxane. In the process of obtaining the MOF material, the metal ions and the organic ligands are combined through coordination bonds to form a MOF material with a network structure. The addition of glacial acetic acid aqueous solution can Improve the reaction rate; in the process of obtaining the MOF / COF composite material, equal volumes of mesitylene and 1,4-dioxane with good solubility are used as a mixed solvent to dissolve the MOF material and the COF monomer, and the addition of glacial acetic acid can increase the reaction rate and promote the polymerization reaction of the COF monomer, so that the COF monomer undergoes polymerization reaction on the surface or inside the MOF material to obtain the MOF / COF composite material. In this process, the mixed solution is subjected to a freezing vacuum treatment to remove impurities such as oxygen and water in the mixed solution, thereby improving the purity and efficiency of the reaction; MOF / COF composite materials and mesitylene are added to the metal cluster solution. In the process of adding toluene, by controlling the temperature and time of the solvothermal reaction, the metal cluster solution (colloid) can replace 1,4-dioxane in the MOF / COF composite material in situ to obtain a MOF / COF composite material with metal clusters embedded in situ; in this process, adding glacial acetic acid can improve the efficiency of the solvothermal reaction; the preparation method embeds the metal clusters into the MOF / COF in situ, and the MOF / COF material anchors the metal clusters to the MOF / COF skeleton or interlayer through the pore or interlayer confinement effect, thereby improving the light capture ability of the MOF / COF material and improving the disadvantage of insufficient catalytic active sites. Furthermore, it can also inhibit the slippage of the COF layer in the MOF / COF material and the escape behavior of the active site due to insufficient anchoring sites, and effectively promote the adsorption and activation of water molecules and reactant furfural molecules at the active center, thereby significantly enhancing the electron and hole separation ability and increasing the furfural hydrogenation reaction rate; for example, in the MOF / COF composite material based on in-situ embedding of metal clusters, the mass ratio of MOF material to COF material can be 1:1, 1:3 or 1:5, and the mass ratio of metal to the MOF material can be 1:200, 1:800, 1:1000, 1:1500 or 1:2000.

[0033] In a third aspect, the present invention provides the application of the above-mentioned MOF / COF composite material based on in-situ embedding of metal clusters in photocatalytic water decomposition and furfural aqueous phase hydrogenation reaction.

[0034] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.

[0035] Unless otherwise specified, the raw materials used in the following examples are commercially available. Example 1

[0036] This embodiment provides a method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters, comprising: S100, obtaining a platinum (Pt) metal disc, placing the metal disc in 1,4-dioxane, controlling the temperature of the 1,4-dioxane to be -20°C, and irradiating the metal disc with a non-focused laser beam under the assistance of ultrasound at a frequency of 20 kHz to obtain a metal cluster solution containing platinum metal particles; the platinum content in the metal cluster solution is 0.1 wt%; the diameter of the metal disc is 15 mm, and the thickness is 5 mm; The output wavelength of the laser beam is 1064nm, the pulse frequency is 20Hz, the output spot diameter is 5mm, and the energy density of the laser beam irradiation is 800mJ / cm 2 , irradiation time is 10min; S200, zirconium chloride and 2-aminoterephthalic acid were added to 15 mL of N,N-dimethylformamide, and ultrasonic dispersion was performed for 20 minutes to make them uniformly mixed, and then 3 mL of glacial acetic acid aqueous solution was added, and the mixture was reacted at 100 °C for 24 hours to obtain the MOF material UiO-66-NH2; The mass ratio of N,N-dimethylformamide to zirconium chloride is 1:2, the mass ratio of zirconium chloride to 2-aminoterephthalic acid is 1:1, the mass ratio of glacial acetic acid to water in the glacial acetic acid aqueous solution is 1:40, and the frequency of ultrasound is 20kHz; S300, dissolving 5 g of the MOF material UiO-66-NH2 and 5 g of the COF monomer in step S200 in a mixed solvent of mesitylene and 1,4-dioxane, adding 50 mL of glacial acetic acid, and performing a solvent thermal reaction for 72 hours after freezing and vacuuming to obtain a MOF / COF composite material; The mass ratio of MOF material UiO-66-NH2 to 1,4-dioxane is 1:0.03, and the mixed solvent is equal volumes of mesitylene and 1,4-dioxane; COF monomers are trialdehyde phloroglucinol (TP) and p-phenylenediamine (Pa-1), and in the MOF / COF composite material, the MOF material is UiO-66-NH2, and the COF material is TPPa-1-COF; S400, adding the MOF / COF composite material and mesitylene in step S300 to 150 mL of the metal cluster solution in step S100, mixing evenly, adding 0.05 mL of glacial acetic acid, and conducting a solvent thermal reaction at a temperature of 100° C. for 72 hours, cooling to room temperature (25° C.), to obtain a MOF / COF composite material with platinum metal clusters in situ embedded; wherein the mass ratio of the metal cluster solution to the MOF / COF composite material is 1:4, and the volumes of mesitylene and the metal cluster solution are equal. Example 2

[0037] This embodiment provides a method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters, comprising: S100, obtaining a platinum (Pt) metal disc, placing the metal disc in 1,4-dioxane, controlling the temperature of the 1,4-dioxane to be 0°C, and irradiating the metal disc with a non-focused laser beam under the assistance of ultrasound at a frequency of 40 kHz to obtain a metal cluster solution containing platinum metal particles; the platinum content in the metal cluster solution is 0.2wt%; the diameter of the metal disc is 20mm, and the thickness is 5mm; The output wavelength of the laser beam is 1064nm, the pulse frequency is 40Hz, the output spot diameter is 10mm, and the energy density of the laser beam irradiation is 1600mJ / cm 2 , irradiation time is 30min; S200, zirconium chloride and 2-aminoterephthalic acid were added to 30 mL of N,N-dimethylformamide, and ultrasonic dispersion was performed for 20 minutes to make them uniformly mixed, and then 1 mL of glacial acetic acid aqueous solution was added, and the mixture was reacted at a temperature of 120 ° C for 18 hours to obtain the MOF material UiO-66-NH2; The mass ratio of N,N-dimethylformamide to zirconium chloride is 1:6, the mass ratio of zirconium chloride to 2-aminoterephthalic acid is 1:3, the mass ratio of glacial acetic acid to water in the glacial acetic acid aqueous solution is 1:60, and the frequency of ultrasound is 20kHz; S300, dissolving 5 g of the MOF material UiO-66-NH2 in step S200 and 20 g of the COF monomer in a mixed solvent of mesitylene and 1,4-dioxane, adding 50 mL of glacial acetic acid, and performing a solvent thermal reaction for 48 hours after freezing and vacuuming to obtain a MOF / COF composite material; The mass ratio of MOF material UiO-66-NH2 to 1,4-dioxane is 1:0.1, and the mixed solvent is equal volumes of mesitylene and 1,4-dioxane; COF monomers are trialdehyde pyrogallol (TP) and p-phenylenediamine (Pa-1), and in the MOF / COF composite material, the MOF material is UiO-66-NH2, and the COF material is TPPa-1-COF; S400, adding the MOF / COF composite material and mesitylene in step S300 to 150 mL of the metal cluster solution in step S100, mixing evenly, adding 50 mL of glacial acetic acid, and conducting a solvent thermal reaction at a temperature of 100° C. for 48 hours, cooling to room temperature (25° C.), to obtain a MOF / COF composite material with platinum metal clusters in situ embedded; wherein the mass ratio of the metal cluster solution to the MOF / COF composite material is 1:6, and the volumes of mesitylene and the metal cluster solution are equal. Example 3

[0038] This embodiment provides a method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters, comprising: S100, obtaining a platinum (Pt) metal disc, placing the metal disc in 1,4-dioxane, controlling the temperature of the 1,4-dioxane to be -10°C, and irradiating the metal disc with a non-focused laser beam under the assistance of ultrasound at a frequency of 30 kHz to obtain a metal cluster solution containing platinum metal particles; the platinum content in the metal cluster solution is 0.3wt%; the diameter of the metal disc is 20mm, and the thickness is 10mm; The output wavelength of the laser beam is 1064nm, the pulse frequency is 30Hz, the output spot diameter is 8mm, and the energy density of the laser beam irradiation is 1300mJ / cm 2 , irradiation time is 20min; S200, zirconium chloride and 2-aminoterephthalic acid were added to 20 mL of N,N-dimethylformamide, and ultrasonic dispersion was performed for 20 minutes to make them uniformly mixed, and then 2 mL of glacial acetic acid aqueous solution was added, and the mixture was reacted at a temperature of 130 ° C for 12 hours to obtain the MOF material UiO-66-NH2; The mass ratio of N,N-dimethylformamide to zirconium chloride is 1:4, the mass ratio of zirconium chloride to 2-aminoterephthalic acid is 1:2, the mass ratio of glacial acetic acid to water in the glacial acetic acid aqueous solution is 1:50, and the frequency of ultrasound is 20kHz; S300, dissolving 5 g of the MOF material UiO-66-NH2 in step S200 and 7.5 g of the COF monomer in a mixed solvent of mesitylene and 1,4-dioxane, adding 50 mL of glacial acetic acid, and performing a solvent thermal reaction for 60 hours after freezing and vacuuming to obtain a MOF / COF composite material; The mass ratio of MOF material UiO-66-NH2 to 1,4-dioxane is 1:0.05, and the mixed solvent is equal volumes of mesitylene and 1,4-dioxane; COF monomers are trialdehyde pyrogallol (TP) and p-phenylenediamine (Pa-1), and in the MOF / COF composite material, the MOF material is UiO-66-NH2, and the COF material is TPPa-1-COF; S400, adding the MOF / COF composite material and mesitylene in step S300 to 150 mL of the metal cluster solution in step S100, mixing evenly, adding 50 mL of glacial acetic acid, and conducting a solvent thermal reaction at a temperature of 100° C. for 60 hours, cooling to room temperature (25° C.), and obtaining a MOF / COF composite material with platinum metal clusters in situ embedded; wherein the mass ratio of the metal cluster solution to the MOF / COF composite material is 1:1.5, and the volumes of mesitylene and the metal cluster solution are equal. Example 4

[0039] This embodiment provides a method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters, comprising: S100, obtaining a copper (Cu) metal disc, placing the metal disc in 1,4-dioxane, controlling the temperature of the 1,4-dioxane to be -10°C, and irradiating the metal disc with a non-focused laser beam under the assistance of ultrasound at a frequency of 30 kHz to obtain a metal cluster solution containing copper metal particles; the copper content in the metal cluster solution is 0.3 wt%; the diameter of the metal disc is 15 mm, and the thickness is 5 mm; The output wavelength of the laser beam is 1064nm, the pulse frequency is 30Hz, the output spot diameter is 8mm, and the energy density of the laser beam irradiation is 1300mJ / cm 2 , irradiation time is 20min; S200, zirconium chloride and 2-aminoterephthalic acid were added to 15 mL of N,N-dimethylformamide, and ultrasonic dispersion was performed for 20 minutes to make them evenly mixed, and then 1 mL of glacial acetic acid aqueous solution was added, and the mixture was reacted at a temperature of 130 ° C for 12 hours to obtain the MOF material UiO-66-NH2; The mass ratio of N,N-dimethylformamide to zirconium chloride is 1:4, the mass ratio of zirconium chloride to 2-aminoterephthalic acid is 1:2, the mass ratio of glacial acetic acid to water in the glacial acetic acid aqueous solution is 1:50, and the frequency of ultrasound is 20kHz; S300, dissolving 5 g of the MOF material UiO-66-NH2 in step S200 and 7.5 g of the COF monomer in a mixed solvent of mesitylene and 1,4-dioxane, adding 50 mL of glacial acetic acid, and performing a solvent thermal reaction for 60 hours after freezing and vacuuming to obtain a MOF / COF composite material; The mass ratio of MOF material UiO-66-NH2 to 1,4-dioxane is 1:0.05, and the mixed solvent is equal volumes of mesitylene and 1,4-dioxane; COF monomers are trialdehyde pyrogallol (TP) and p-phenylenediamine (Pa-1), and in the MOF / COF composite material, the MOF material is UiO-66-NH2, and the COF material is TPPa-1-COF; S400, adding the MOF / COF composite material and mesitylene in step S300 to 150 mL of the metal cluster solution in step S100, mixing evenly, adding 50 mL of glacial acetic acid, and conducting a solvent thermal reaction at a temperature of 100° C. for 60 hours, cooling to room temperature (25° C.), to obtain a MOF / COF composite material with copper metal clusters in situ embedded; wherein the mass ratio of the metal cluster solution to the MOF / COF composite material is 1:1.5, and the volumes of mesitylene and the metal cluster solution are equal.

[0040] Through the above-mentioned Examples 1 to 4, the present invention prepares MOF / COF composite materials with different metal clusters embedded in situ, see Figures 1 to 13 ,from Figure 1 It can be seen that MOF / COF composite materials (composite catalysts) have excellent capabilities in photocatalytic water decomposition to produce hydrogen and furfural hydrogenation to achieve high value utilization. Figure 2 It can be seen that the prepared MOF material UiO-66-NH2 is a spherical particle with a size of about 200nm; Figure 3 It can be seen that the prepared COF material TPPa-1-COF presents a two-dimensional dendritic nanostructure; Figure 4 It can be seen that in the prepared MOF / COF composite material (Pt@MOF / COF composite material) in which platinum metal clusters are in situ embedded, the size of the Pt clusters is 1~2nm; Figure 5 It can be seen that in the prepared Pt@MOF / COF composite material, the larger Pt nanoparticles of 3-5 nm are distributed between the MOF / COF layers, and the Pt nanoclusters grow due to the weak anchoring force of the MOF material. Figure 6 It can be seen that in the prepared MOF / COF (1:1) composite material, COF nanowires are entangled on the surface of MOF nanoparticles to form a stable two-dimensional / three-dimensional mixed-dimensional structure; Figure 7 This is a physical picture of MOF / COF (1:1), the color is blood red; Figure 8 It can be seen that in the prepared MOF / COF (1:4) composite material, MOF nanoparticles are embedded on the dendritic COF; Fig. 9 This is a physical picture of MOF / COF (1:4), the color is blood red; Fig.10It can be seen that in the prepared MOF / COF (2:3) composites, MOF nanoparticles are embedded on the dendritic COF, which is due to the fact that COF is more than the MOF component; Fig.11 This is a physical picture of MOF / COF (2:3), the color is blood red, mainly the color of COF; Fig.12 From the performance diagram of the catalysts for photocatalytic water decomposition to produce hydrogen, the hydrogen production rate of the Pt0.3@MOF / COF (1:1) catalyst is as high as 101.1 mmol g -1 h -1 , is the best catalyst among similar materials; Fig.13 From the performance diagram of the photocatalytic hydrogenation of furfural under different catalysts, as the Pt loading increases from 0.05wt% to 0.2wt%, the conversion rate of furfural reaches 100%, and the hydrogenation products are all tetrahydrofurfuryl alcohol. However, as the Pt content continues to increase to 0.3wt%, the product of furfural hydrogenation gradually changes to 2-methylfuran. This is because the high activity density of Pt sites reduces the barrier of furfural hydrogenation and deoxygenation. When the Pt content continues to increase, by-products are found. This is because when the Pt content exceeds 0.3wt%, Pt will aggregate and reduce its activity.

[0041] In summary, the present invention uses liquid phase pulse laser technology to embed metal clusters in situ in MOF / COF; the basic process can be: first select high-purity metal platinum, copper, cobalt, nickel sources and 1,4-dioxane (Diox), then use extreme condition transient pulse laser irradiation technology to directly prepare metal cluster solutions of Pt (Diox), Cu (Diox), Co (Diox), and Ni (Diox), and then use the above metal cluster solution as a solvent for synthesizing MOF / COF, and obtain a MOF / COF composite material with in situ embedded metal clusters through a one-pot reaction, and the size and content of metal particles in the metal cluster solution or the MOF / COF composite material can be controlled. The present invention uses component feed ratio control to prepare a MOF / COF composite material with controllable micromorphology. In the MOF / COF composite material, when the content of MOF material is higher than that of COF material, the COF material is wrapped around the MOF material in a nanowire structure to form a COF covering layer; when the content of MOF material is lower than that of COF material, MOF nanoparticles are dispersed on the dendritic COF. Furthermore, through the technical solution of the present invention, metal clusters with electron traps and catalytic active sites are in situ embedded in MOF / COF with different structures, and a metal-organic framework-bridged covalent organic framework composite catalyst with in situ anchored metal clusters is prepared. The light capture ability of MOF / COF can be regulated to improve the disadvantage of slow separation kinetics of charge carriers, and promote the water decomposition kinetics and the hydrogenation rate of biomass derivatives; further, MOF / COF anchors the metal clusters to the MOF / COF skeleton or interlayer through the pore or interlayer confinement effect, thereby improving the disadvantages of poor light capture ability and insufficient catalytic active sites of MOF, not only inhibiting the sliding of the COF layer and the escape behavior of the active sites due to insufficient anchoring sites, but also promoting the adsorption-activation of water molecules and reactant furfural molecules at the active center, thereby significantly enhancing the electron-hole separation ability and increasing the furfural hydrogenation reaction rate.

[0042] In the description of the above embodiments, specific features, structures, materials or characteristics may be combined in a suitable manner in any one or more embodiments or examples.

[0043] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters, characterized in that: include: Obtaining a metal target material, placing the metal target material in 1,4-dioxane, and irradiating the metal target material with a laser beam under the assistance of ultrasound to obtain a metal cluster solution containing metal particles; Add metal salt and organic ligand to N,N-dimethylformamide, mix well, add glacial acetic acid aqueous solution, and react at a temperature of 100-130° C. for 12-24 hours to obtain MOF material; The MOF material and COF monomer are dissolved in a mixed solvent of mesitylene and 1,4-dioxane, and glacial acetic acid is added, and after freezing and vacuuming, the solvent thermal reaction is performed for 48 to 72 hours to obtain a MOF / COF composite material; The MOF / COF composite material and mesitylene are added to the metal cluster solution, mixed evenly, and then glacial acetic acid is added. The mixture is subjected to solvent thermal reaction at a temperature of 100 to 130° C. for 48 to 72 hours. After cooling, a MOF / COF composite material with metal clusters embedded in situ is obtained.

2. The method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters according to claim 1, characterized in that: The metal target comprises one or more of a platinum target, a copper target, a cobalt target and a nickel target; and / or, The metal target material is a metal disc.

3. The method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters according to claim 2, characterized in that: The metal salts include zirconium chloride, ferric chloride, hydrated copper nitrate and tetraisopropyl titanate; and / or, The organic ligands include 2-aminoterephthalic acid, 2,5-diaminoterephthalic acid and 2-hydroxyterephthalic acid.

4. The method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters according to claim 3, characterized in that: The COF monomers include trialdehyde phloroglucinol and p-phenylenediamine; and / or, In the process of adding the MOF / COF composite material and mesitylene into the metal cluster solution, the mass ratio of the metal cluster solution to the MOF / COF composite material is 1:(4-6), and the volumes of the mesitylene and the metal cluster solution are equal.

5. The method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters according to claim 4, characterized in that: The metal cluster solution is a colloidal solution; and / or, The content of metal particles in the metal cluster solution is 0.05-0.5wt%.

6. The method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters according to claim 5, characterized in that: In the process of irradiating the metal target material with a laser beam under the assistance of ultrasound, the laser beam includes an unfocused laser beam; and / or, The output wavelength of the laser beam is 1064nm, the pulse frequency is 20-40Hz, the output spot diameter is 5-10mm, and the energy density of the laser beam irradiation is 800-1600mJ / cm 2 , irradiation time is 10~30min; and / or, The temperature of the 1,4-dioxane is -20 to 0°C, and the frequency of the ultrasound is 20 to 40 kHz.

7. The method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters according to claim 6, characterized in that: In the process of adding the metal salt and the organic ligand to N,N-dimethylformamide, the mass ratio of the metal salt to the organic ligand is 1:(1-3), and the mass ratio of the N,N-dimethylformamide to the metal salt is 1:(2-6); and / or, The mass ratio of glacial acetic acid to water in the glacial acetic acid aqueous solution is 1: (40-60).

8. The method for preparing a MOF / COF composite material based on in-situ embedding of metal clusters according to claim 7, characterized in that: The MOF material and the COF monomer are dissolved in a mixed solvent of mesitylene and 1,4-dioxane, wherein the mass ratio of the MOF material to the COF monomer is 1:(1-5), the mass ratio of the MOF material to the 1,4-dioxane is 1:(0.03-0.1), and the volumes of mesitylene and 1,4-dioxane in the mixed solvent are equal; and / or, In the MOF / COF composite material in which the metal clusters are in-situ embedded, the mass ratio of the MOF material to the COF material is 1:(1-5), and the mass ratio of the metal to the MOF material is 1:(200-2000).

9. A MOF / COF composite material based on in-situ embedding of metal clusters, prepared by the preparation method of a MOF / COF composite material based on in-situ embedding of metal clusters according to any one of claims 1 to 8; in the MOF / COF composite material based on in-situ embedding of metal clusters, the mass ratio of MOF material to COF material is 1:(1-5), and the mass ratio of metal to the MOF material is 1:(200-2000).

10. Use of the MOF / COF composite material based on in-situ embedding of metal clusters according to claim 9 in photocatalytic water decomposition and furfural aqueous phase hydrogenation reaction.

Citation Information

Patent Citations

  • Visible light photocatalyst for in-situ synthesis of hydrogen peroxide as well as preparation method and application of visible light photocatalyst

    CN115888823A

  • MOFs composite catalyst for in-situ implantation of multi-component metal nano colloidal particles as well as preparation method and application of MOFs composite catalyst

    CN116371472A

  • Preparation method and application of core-shell-shaped MOF (at) COF heterojunction material

    CN118122381A

  • Metal nanoparticle confinement covalent organic framework material and preparation method thereof

    CN118388791A

  • Metal nanocluster capable of keeping stable for long time and preparation method of metal nanocluster

    CN118492360A